Your Career In The Army - Jason Porterfield
Today's Army has over 675,000 active duty and reserve soldiers in service. There are more than 150 Army careers, and this guide gives readers essential vocational information they need before deciding to enlist. Careers within a number of disciplines, including engineering, finance, medicine, human resources, law enforcement, psychology, computer technology, construction, and law are entertainingly covered. Also included is information about available options for life after the Army, such as through the Army Reserves and the Army Corps of Engineers. A detailed resources section helps point readers in the right direction to learn more about life in this military institution. With such a comprehensive view into the Army and all it has to offer, this book will help readers make an informed decision about whether serving is the right move for them.